Accounting for ignorance: An investigation into corruption, immigration and the state. (July 2022) - Pianezzi, Daniela; Ashraf, Muhammad Junaid
Highlights: Ignorance relieved the Italian state of the burden of the refugee crisis. Accounting plays a role in producing and sustaining ignorance. Corruption becomes a collateral damage to achieve a greater 'public' benefit. Critical realism allows the investigation of the strategic use of ignorance. Abstract: This research aims to investigate the financial and immigration mismanagement in Italy in the context of the recent refugee crisis. The paper contributes to previous accounting studies on corruption and immigration by unveiling the role of accounting as a technology of ignorance serving multiple and contradictory objectives of a fragmented State. We observed that ignorance partially produced through accounting relieved the Italian state of the social, political and economic burden of the refugee crisis. As opposed to a common understanding of corruption as use of public office for private gains, the consequent lack of control and corruption deriving from this ignorance ultimately served 'public' gains. The paper proposes retroduction as an approach for conducting critical accounting studies and invites future accounting researchers to expose States' control over territory, resources, and population through a critical investigation of the strategic and political use of ignorance.